Report on the state of public health in Canada 2011 : youth and young adults - life in transition (Public Health Agency of Canada OttawaCA, 2011)
Aims to inform Canadians and to stimuate a dialogue on the many factors that contribute to good health and what the society can do to advance public health in Canada.Highlights areas where collective action can be taken to ensure the best possible future for youth.
Keywords: PUBLIC HEALTH